Gamma-ray emission from Cassiopeia A produced by accelerated cosmic rays - Berezhko, Evgeny; Pühlhofer, Gerd; Völk, Heinrich J. (ICRC 2001, 2001)
The kinetic nonlinear model of cosmic ray (CR) acceleration in supernova remnants (SNRs) is used to describe the relevant properties of the Cas A remnant. We use the model of a locally smooth circumstellar medium developed by Borkowski et al. (1996) which consists of a tenuous inner bubble, a dense shell of swept-up slow red supergiant wind material, and a subsequent red supergiant wind region, in order to reproduce the SNR’s observed size, expansion rate and thermal X-ray emission. The values of other physical parameters which inﬂuence the CR acceleration are taken to ﬁt the observed synchrotron emission of Cas A in the radio and X-ray range. The calculated integral γ-ray ﬂux from Cas A is dominated by π0-decay γ-rays produced by relativistic protons. It extends up to almost 100 TeV and at TeV-energies considerably exceeds the value 5.8 × 10−13 cm−2s−1 detected by the HEGRA collaboration (Aharonian et al., 2001). Possible explanations of this discrepancy are proposed which correspond either to leakage of the highest energy CRs from the remnant already at the current stage, to a lower gas density, or to an unusually high electron to proton ratio for the accelerated CRs.